Performance evaluation approach for design space explorations of propulsive fuselage aircraft concepts - Moirou, Nicolas G. M.; Sanders, Drewan S. (Springer, 2025)
A promising architecture to enhance the performance of next-generation commercial aircraft involves embedding the propulsion system within the airframe, thereby capturing energy from the fuselage through boundary layer ingestion. However, in cases of strong aerodynamic coupling, traditional accounting methods break down, necessitating alternative approaches. The lack of consensus surrounding the interpretation and quantification of these benefits underscores the need for a unified assessment method. In this work, commonly used near-field momentum-based bookkeeping schemes are discussed and unified with a more holistic energy-based approach to evaluate aero-propulsive performance and facilitate more intuitive physical interpretations of the aerodynamics. The contribution of this work lies in the correction of the power balance, leading to the development of new metrics for assessing the efficiencies of both the aircraft and the boundary layer ingestion propulsion system. Notably, a surrogate for propulsive efficiency and limits to the power saving coefficient are given, which address inconsistencies present in the literature. Despite their application to an axi-symmetric propulsive fuselage, the metrics introduced are applicable to higher levels of representativity of propulsive fuselage concepts. The potential impact of this work is the transformation of established evaluation practices by employing these newly introduced metrics to assess aircraft and system efficiencies.
Keywords: 40 Engineering; 4001 Aerospace Engineering; Generic health relevance